2011
DOI: 10.1590/s0103-50532011000300012
|View full text |Cite
|
Sign up to set email alerts
|

Solution properties of a hydrophobically associating polyacrylamide and its polyelectrolyte derivatives determined by light scattering, small angle x-ray scattering and viscometry

Abstract: Uma poliacrilamida hidrofobicamente modificada e dois dos seus derivados parcialmente hidrolisados, contendo grupos hidrofóbicos e carboxila, foram preparados por polimerização micelar e pós-hidrólise. A massa molar, o segundo coeficiente do virial e o raio de giração foram determinados por espalhamento de luz estático (SLS). O espalhamento de luz dinâmico (DLS) e o espalhamento de raios-X a baixos ângulos (SAXS) foram utilizados respectivamente para determinar a formação de agregados e o tipo de empacotamento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
2
6
0
1
Order By: Relevance
“…Simon et al (2003) observed that the K H for amphiphilic derivatives of carboxymethyl pullulans increased with increasing degree of hydrophobic modification. This trend has also been reported for hydrophobically modified derivatives of dextran (Rotureau et al 2006), polyacrylamide (Maia et al 2011) and carboxymethylcellulose (CharpentierValenza et al 2005). These studies attributed the increase in K H to increasing polymer-polymer interaction and decreasing polymer-solvent interaction, which could also be referred to as the formation of a reversible network by supramolecular aggregation.…”
Section: Calculation Of Intrinsic Viscositysupporting
confidence: 65%
See 4 more Smart Citations
“…Simon et al (2003) observed that the K H for amphiphilic derivatives of carboxymethyl pullulans increased with increasing degree of hydrophobic modification. This trend has also been reported for hydrophobically modified derivatives of dextran (Rotureau et al 2006), polyacrylamide (Maia et al 2011) and carboxymethylcellulose (CharpentierValenza et al 2005). These studies attributed the increase in K H to increasing polymer-polymer interaction and decreasing polymer-solvent interaction, which could also be referred to as the formation of a reversible network by supramolecular aggregation.…”
Section: Calculation Of Intrinsic Viscositysupporting
confidence: 65%
“…Although this is expected owing to the lower molecular mass of hmHEC compared to that of the HEC, the presence of hydrophobic associations ) and the empirical constants obtained from Huggins, Kraemer and Schulz-Blaschke equations for all set A and B polymers and the concentration c NL at which the corresponding data exhibits a deviation from Huggins equation also cause the collapse of the coil, making it more compact and resulting into a lower value of intrinsic viscosity. This phenomenon has been reported for the hydrophobically modified derivatives of many polymers such as dextran (Rotureau et al 2006;Durand 2007a, b), carboxymethyl cellulose (CharpentierValenza et al 2005), polyacrylamide (Maia et al 2011) and hmHEC (Maestro et al 2002a). However, for set B polymers the intrinsic viscosity values of amphiphilic derivatives are higher than that of the corresponding non-associative derivative.…”
Section: Calculation Of Intrinsic Viscositysupporting
confidence: 51%
See 3 more Smart Citations